Structure and Chemical Composition Analysis of the Evolutionary Stages of a Primary Star with a Mass of Tipe Algol - M. Abu Kamal (Interdisciplinary Journal of Social Science and Education (IJSSE), 2023)
Modeling using the STARS toolkit to analyze the structure and chemical composition of 2.24M⊙-mass Algol-type primary stars. Algol-type stars are close binary systems that experience the Algol paradox. The Algol paradox is a situation where a star with a smaller mass has evolved further than a star with a larger mass. The results of this modeling are (1) HR diagram (2) graph of stellar structure and (3) graph of stellar chemical composition as a function of radius.